Integration Of Local Leafy Forage In Smallholder Pig Farming And Its Implications For The Nutritional Quality Of Pork Jerky With Added Subcutaneous Fat - Rotinsulu, Merri D.; Hadju, R; Manangkot, H. S.; Sakul, Syalom; Lontaan, Nova (Jurnal Agroekoteknologi Terapan (Applied Agroecotechnology Journal), 2025)
Integrating locally produced leafy forage into smallholder pig systems may influence the nutritional quality of value-added meat products. This study evaluated pork jerky manufactured with different levels of added subcutaneous fat using carcasses from pigs raised in smallholder farms where local leafy forage formed part of the diet. Leafy forage and jerky were characterised by proximate analysis. A completely randomized design with five treatments (0, 10, 20, 30 and 40% added subcutaneous fat; R0–R4) and five replications was used. Increasing added fat from 0 to 40% reduced jerky moisture (40.10 to 32.80%), ash (9.92 to 5.42%) and crude protein (41.21 to 24.67%), while crude fat (8.19 to 28.44%) and carbohydrate by difference (0.58 to 8.67%) increased markedly (P < 0.05). Thus, subcutaneous fat level is a major lever for modifying the energy density and macronutrient profile of pork jerky. From an agricultural systems perspective, these findings illustrate how carcass utilisation and simple on-farm processing can add value to pigs fed partly on local leafy forage and support small-scale agroindustry. Moderate fat inclusion appears to offer a practical compromise between maintaining protein content and enhancing sensory attributes. Keywords: Pork jerky; subcutaneous fat; leafy forage; smallholder pig farming; proximate composition; crop–livestock integration